Mengaktualisasikan strategi pelayanan misi kontekstual kiai Sadrach pada era posmodern - Sostenis Nggebu (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
This research aims to show the holistic mission of the Pentecostal perspective, which departs from the Christian concept of holistic mission, namely Missio Dei, where God initiates mission. The trinitarian framework of sending becomes a biblical philosophical foundation for understanding the Christian mission centered on God rather than the church, a shift from an ecclesiocentric mission to a theocentric mission. The church's place is important as the administrator of God's work in the world. The method used is descriptive qualitative with a library research approach, which brings the concept of holistic Christian mission, in general, closer to the potential of Pentecostal pneumatic spirituality. Suppose the Pentecostal movement can continue to realize the potential of a friendly pneumatic spirituality (hospitality) and embrace all of creation. In that case, that solid mission drive will enable Pentecostals to present the church as an administrator of social justice.Â AbstrakTujuan dari penelitian ini untuk menunjukkan misi holistik perspektif Pentakostal yang bertolak dari konsep misi holistik Kristen, yakni Missio Dei, di mana Allah sebagai inisiator misi. Kerangka pengutu-san trinitarian menjadi fondasi filosofis alkitabiah untuk memahami misi Kristen yang berpusat pada Allah ketimbang gereja, sebuah pergeseran dari ecclesiocentric mission ke theocentric mission. Tempat gereja menjadi pen-ting sebagai administrator dari pekerjaan Allah di dunia. Metode yang di-pergunakan adalah kualitif deskriptif dengan pendekatan library research yang mendekatkan konsep misi holistik Kristen pada umumnya dengan pontensi spritualitas pneumatik Pentakostal. Jika gerakan Pentakostal da-pat terus menyadari akan potensi spiritualitas pneumatik yang ramah (hospitalitas) dan merangkul semua ciptaan, maka dorongan misi yang kuat itu memungkinkan orang-orang Pentakostal mampu menghadirkan gereja sebagai administrator keadilan sosial.